Sztuka słuchania, sztuka mówienia. Miejsce i rola absolwentów kierunków humanistycznych w Public Relations - Marcin Kępiński (Etnografia Polska, 2012)
Showing the place and the role of the graduates of humanistic departments (faculties of arts) in the area of public relations is the aim of this article. These lines, despite obvious differences resulting from the range and the object of the scientific reflection, have a lot in common. The three following fields of study; journalism, sociology and cultural anthropology attribute a great role to communication, language and their influence on the individual, group and culture. Also, for many lecturers, who also function as various experts, advisors, journalists or simply people appearing in media, a very important form of work with their students is interpersonal communication.